Pengaruh Media Quenching Terhadap Sifat Keras dan Struktur Mikro Baja Laterit AISI 3120H - Satrio Herbirowo; Saefudin Saefudin; Toni Bambang Romijarso (Jurnal Metalurgi dan Material Indonesia, 2018)
Has conducted research about heat treatment process at the temperature of 975°C and holding time for 1 hour. Raw material was lateritic steel using material standard AISI 3120 H, which has a content of chemical composition as follows, C = 0.17350%, Si = 0.26981%, S = 0.0283%, P = 0.0232%, Mn = 0.47644%, Ni = 1.19345%, Cr = 0.66948%, Mo = 0.00237%, V = 0.00750%, Cu = 0.03318%, W = 0.00151%, Ti = 0.00771%, Sn = 0.01150%, Al = 0.04419%, Pb = 0.00480, Nb = 0.00743%, Zr = 0.00395%, Zn = 0.00574%, Fe = 97.0309%. whereas this material has a ferrite and pearlite phase and also surface hardness value until 18,54 HRC. The material after heating process using water, oil and air (normalizing) quench media to obtained variety of hardness results. The results of hardness characterization are 47.32 HRC (water quench), quench with oil obtained 33.94 HRC and results of normalizing cooling treatment hardness obtained 14.58 HB. The highest hardness properties are obtained using water quench and the second is using oil quenching, for the microstructure properties there is martensite phase growth all of surface material using all media quench except air quench (normalizing) has a pearlite phase dominant and size smaller than martensite.